A Review of Customer Benefits and Satisfaction in Amanah Product of Pegadaian Syariah Makassar - Siti Walida Mustamin; Jasri Jasri; Widya Nur Indahsari (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2023)
This study aims to evaluate the benefits and satisfaction provided by Amanah Products at Pawnshop Syariah Makassar Branch. This article uses a qualitative research approach with a focus on descriptive analysis. The results of this study reveal that the Amanah Product at Pawnshop Syariah offers easy, structured, and inclusive requirements and procedures, facilitating various groups of individuals such as civil servants, employees, and micro entrepreneurs to obtain vehicle financing without difficulty. The transparent application process also assists customers in fulfilling their vehicle needs. The quality of service presented has met customer expectations. The professionalism shown by the employees of Pawnshop Syariah Makassar Central Branch also gives a positive impression to consumers. Overall, both aspects of the process, transparency, service, and professionalism at the Makassar Central Branch Sharia Pawnshop have met the standards of Islamic law.